Correction: Molecular Epidemiology of Agents of Human Chromoblastomycosis in Brazil with the Description of Two Novel Species. - PLOS Neglected Tropical Diseases Staff (Public Library of Science (PLoS), 2017)
[This corrects the article DOI: 10.1371/journal.pntd.0005102.].